PELATIHAN PRODUKSI OLAHAN HASIL PERIKANAN BERDASAR PRINSIP SANITASI DAN HYGIENE PADA KELOMPOK POKLAHSAR MINA ARGO BERKAH DI KABUPATEN BOJONEGORO PROVINSI JAWA TIMUR - Eka Saputra; Laksmi Sulmartiwi; Arif Habib Fasya; Hapsari Kenconojati; Dwi Yuli Pujiastuti; Annur Ahadi Abdillah; Ahmad Shofy Mubarak; Adriana Monica Sahidu (Jurnal Abdi Insani, 2026)
Community Service (PKM) is a form of knowledge and technology transfer from universities to the community to improve the capacity and welfare of the target population. This PKM activity aims to increase the added value of catfish cultivation through product diversification and the application of appropriate technology to catfish processing and marketing groups (Poklahsar) in Tlogorejo Village, Bojonegoro Regency. The implementation method includes field observation, problem identification, outreach, training, and hands-on product processing practice. The main challenge faced by partners is limited knowledge and skills in processing catfish into value-added products, resulting in the harvest generally being sold fresh with relatively low economic value. Therefore, training is provided on catfish-based product diversification and mentoring on the application of appropriate technology to produce safe and high-quality products. The results of the activity indicate that partners are able to produce a variety of diversified processed catfish products, including catfish nuggets, catfish dumplings, and catfish dragon legs. The application of appropriate processing technology contributes to improving product quality, consumer acceptance, and potential sales value. Furthermore, this activity enhances partners' knowledge and skills in fishery product processing and opens up opportunities for developing businesses based on processed catfish products. This Community Service Program (PKM) activity is expected to serve as a model for empowering catfish farmers by increasing the added value of their aquaculture products, expanding fishery product diversification, and supporting local income and food security.